Evaluation of Molecular Markers and Morphology In Identification of Local Porang Strain in Karawang District - Komariah, Ai; Romiyadi; Dyah Setya Wuryani; Luthful Hakim; Nunung Sondari; Lia Amalia; Muhammad Subandi (Green Publisher, 2023)
Porang plant tubers have the potential to have high economic value, because they contain glucomannan which is good for health and can be processed into a food source to replace carbohydrates. The aim of the study was to identify Karawang Local Porang strains using molecular markers and morphological characters as an effort to conserve and utilize Karawang's local biological resources. Exploration of Local Porang Karawang was carried out at the foot of Mount Sanggabuana which is the habitat of Porang in Karawang district. Molecular identification was carried out at BBPP Biotechnology and Agricultural Genetic Resources with comparisons of Porang Sidrat., Madiun 1 and SS1 Bulukumba varieties. Morphological identification was carried out at the Basic Laboratory of the Faculty of Agriculture, Winaya Mukti University. Based on the results of the DNA amplification of the Porang samples using four RAPD primers, it was found that the three primers showed differences in banding patterns between the Porang Karawang sample and the three Porang varieties for comparison (Porang Madiun 1 Sidrap and SS1 Bulukumba). This shows that there is genetic variation between Porang from Karawang and three other Porang. The results of genetic relationship analysis using four RAPD primers showed that the Porang Karawang sample was different from the Porang samples from the other two areas. The morphological identification results showed differences in characteristics with the comparison. The Karawang Local Porang variety has high quality as indicated by high glucomannan levels of 79.80%.